Karakteristik Aspal Beton Lapis Aus (AC-WC) Dengan Penambahan Bahan Pengisi Abu Terbang Batubara - M.Sa'dillah; Leliana , Arinda (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Efforts to increase the strength of the pavement structure in addition to a new specific hot asphalt mixture, the choice of the material type also has a big role. The material in question other than asphalt, coarse, and fine aggregate contains filler. Cement materials and coal fly ash are the best materials that can be used as fillers. Coal fly ash is the residue of burning coal at a Steam Power Plant (PLTU) so that in this study it is used as a filler in a mixture asphalt concrete wearing course (AC-WC). In this study, it is divided into 3 (three) stages (1) the stage of selecting materials; (2) the test object preparation stage; (3) the research and data analysis stage. From the test results, the materials for coarse and fine aggregate, filler and asphalt are in accordance with the required specifications. The addition of coal fly ash filler proved that there was an increase in the stability of the asphalt concrete mixture. The more it is added, the stability value will also increase. Apart from the stability value, VIM and VMA values ​​are also affected. The more the coal fly ash filler content is added, the smaller the cavity of the asphalt concrete mixture so that the mixture is more waterproof and the gap (empty space) between the aggregates is also getting smaller. This shows that coal fly ash functions to fill the gaps between the aggregates so that it becomes an interlocking in the asphalt concrete mixture